The Impact of The Use of Combine Harvester on The Income of Rice Farmer in Pemangkat District Sambas Regency - Asrita; Yurisinthae, Erlinda; Suyatno, Adi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Farmers' income is not always high, sometimes it can be very low and experience losses. This is due to several things that can cause a decrease in rice yields caused by the loss of grain due to the manual harvesting process, as well as the high cost of production and harvesting processes. The purpose of this study was to evaluate the impact of the use of a combine harvester on the farmer's economy, especially on the farmer's income by comparing the level of income between farmers who use a combine harvester and farmers who harvest manually in the Pemangkat District area, and analyze the factors that influence the adoption of combine harvester technology. This study was conducted in Pemangkat District, Sambas Regency, West Kalimantan with 44 respondents. The research variables were income, revenue, production yield, selling price and production costs. This study used the Independent Sample T test using the Saphiro Wilk data normality test, Levene's variance homogeneity test, and t test. From the results of the study, it can be concluded that farmers' income experienced a significant difference between farmers who used combine harvester machines and farmers who used manual harvesting. Based on the results of analysis and observations, the use of combine harvester machines significantly reduces production and harvesting costs so that it can increase farmers' income, so farmers should consider switching to using machines to harvest rice to increase farmers' income.